PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN NIAS SELATAN - Konstantinus Kesadaran Daeli (Universitas Nias Raya, 2022)
This study aims to determine how much influence motivation and job satisfaction have on employee performance at the Office of the Population and Civil Registration Office of South Nias Regency. The research used is a type of quantitative research that is associative. The data source is an official with the population and the sample in this research is 37 respondents. The data collection technique is using a questionnaire. Data analysis method used is multiple linear regression analysis method. The research result for the fisrt partial test (T test) between work motivasion(X1) on employee performance (Y) is Tcount(2,051) > Ttable(1,690), and for the secont partial test beetwen job satisfaction(X2) on employee performance(Y) is Tcount(2,297) > Ttable(1,690) this shows that the variables of motivation and job satisfaction have a significant effect on employee performance. The research results for simultaneous test (F test) value of FCount (6,381) > FTable (3,276)means that the variables of motivation and job satisfaction simultaneously or simultaneously affect employee performance variables at the population and civil registration office of south nias regency. The value of the regression equation Y=24,817 + 0,269X1 + 0,274X2. The suggestions is this research are (1) the leadership of the civil registration and population office of south nias regency should always pay attention to the performance of its officers whether they have been working in accordance with the rules that have been set or not. (2) Giving motivation to its officers and also pay attention to the job satisfaction of its officers so that the officers work to the maximum.